Avian species-assemblage structure and indicator bird species of mangroves in the Australian monsoon tropics - J., Mohd Azlan; Noske, R.A; Lawes, M.J (BirdLife Australia, 2015)
Mangroves are threatened worldwide yet they host diverse avian assemblages, especially in Australia. We examined the diversity, density and habitat use of birds in northern Australian mangroves to determine the influence of habitat patch-size and floristic composition on the structure of mangrove bird assemblages. Birds were surveyed using line transects in 13 mangrove patches. A total of 70 species was encountered, with a mean density of 11.7 individuals ha–1,including 11 of 12 known mangrove-dependent species. Many species were strongly associated with, and indicative of, a specific mangrove plant zone, emphasising the importance of the number of zones to bird diversity at a site. Of six functional guilds, the insectivores were most dominant, followed by nectarivores. Accordingly, avian assemblage structure was influenced by mangrove flowering phenology. Large mangrove patches supported fewer species than many smaller patches of equivalent combined area, and species richness was independent of area. In addition, there was no density compensation or a density–area relationship, implying that assemblages are not saturated with species and species interactions do not determine assemblage structure. In order of increasing importance, avian assemblage structure in mangroves is determined by the type and diversity of mangrove zones, the timing of mangrove flowering and the nature of the matrix surrounding mangroves.